Chemical characterization and FTIR spectroscopy of thermally compressed eucalyptus wood panels - Oktay Gonultas; Zeki Candan (Maderas: Ciencia y Tecnología, 2018)
In this study, the change in the chemical properties of the thermally modified eucalyptus (Eucalyptus camaldulensis) wood boards were examined by wet chemical analysis and FTIR spectroscopy. The eucalyptus wood boards were modified with a laboratory type hot-press for four different groups at press pressures of 2 or 4 MPa and temperatures of 150°C or 180°C and compared to untreated control. After this, hot water, 1% NaOH, ethanol-cyclohexane, ethanol, and methanol-water solubility values were determined for the treated samples. In addition, the content of klason lignin, acid soluble lignin, holocellulose, and α-cellulose were investigated. The solubility values (except for the ethanol solubility) increased in the modified wood when compared to the untreated control. A decrease in the content of acid soluble lignin, holocellulose and α-cellulose was observed while the content of klason lignin in the modified wood was increased. According to the FTIR analysis results, significant changes were observed in the spectra of the modified samples. These findings were in agreement with the results of wet chemical analysis.